The Health Counseling On Hypertension and Blood Pressure Checking in Sungai Tiung RT.32 Communities Working Area Of Cempaka Community Health Center - Fauziah, Erna; Mariana, Evi Risa; Sajidah, Ainun; Annisa, Mutia; Dilla, Silviya (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
ABSTRAK Hypertension is a condition in which a person experiences an increase in blood pressure above normal which results in morbidity and mortality. Hypertension is often referred to as the silent killer because it is deadly without being accompanied by its symptoms as a warning to its victims. With the Implementation of Community Service Activities it is hoped that the Lecturers of the Nursing Department of the Banjarmasin Ministry of Health Poltekkes can contribute to the community to improve health status, especially in the health sector of Non-Communicable Diseases (PTM). The implementation of Community Service Activities was carried out with 2 main activities starting with the first activity, namely the Implementation of Health Education about Hypertension once, followed by an evaluation in the form of distributing questionnaires to participants and providing opportunities to ask questions. In the second activity, namely Checking Blood Pressure in the Community. The targets of this activity consisted of 6 young women, 21 adult women, and 13 elderly women who are residents of the Sungai Tiung sub-district, RT. 32 Banjarbaru City. After counseling the PKM participants had good knowledge about hypertension as many as 30 people (75%) and there were still 10 people (25%) who had sufficient knowledge. Questionnaire question number 8 (hypertension always causes symptoms/complaints) received the most wrong answers from counseling participants (the community/mothers) as many as 36 people (90%) this means that people still think that hypertension always causes symptoms/complaints, so it is necessary to hold health promotion about hypertension which does not always cause symptoms, as well as motivating people to check their blood pressure regularly even if there are no symptoms.